Resting-state Functional Magnetic Resonance Imaging Correlates of Sevoflurane-induced Unconsciousness. (August 2015) - Palanca, Ben Julian A.; Mitra, Anish; Larson-Prior, Linda; Snyder, Abraham Z.; Avidan, Michael S.; Raichle, Marcus E.
Abstract : Background: Blood oxygen level–dependent (BOLD) functional magnetic resonance imaging (fMRI) has been used to study the effects of anesthetic agents on correlated intrinsic neural activity. Previous studies have focused primarily on intravenous agents. The authors studied the effects of sevoflurane, an inhaled anesthetic. Methods: Resting-state BOLD fMRI was acquired from 10 subjects before sedation and from 9 subjects rendered unresponsive by 1.2% sevoflurane. The fMRI data were analyzed taking particular care to minimize the impact of artifact generated by head motion. Results: BOLD correlations were specifically weaker within the default mode network and ventral attention network during sevoflurane-induced unconsciousness, especially between anterior and posterior midline regions. Reduced functional connectivity between these same networks and the thalamus was also spatially localized to the midline frontal regions. The amplitude of BOLD signal fluctuations was substantially reduced across all brain regions. The importance of censoring epochs contaminated by head motion was demonstrated by comparative analyses. Conclusions: Sevoflurane-induced unconsciousness is associated with both globally reduced BOLD signal amplitudes and selectively reduced functional connectivity within cortical networks associated with consciousness (default mode network) and orienting to salient external stimuli (ventral attention network). Scrupulous attention to minimizing the impact of head motion artifact is critical in fMRI studies using anesthetic agents. Abstract : Sevoflurane-induced unconsciousness leads to a widespread reduction in brain activity. Functional connectivity is selectively reduced within the default mode and ventral attention networks. Motion artifact, a prevalent confounding variable in functional magnetic resonance imaging studies involving anesthetic agents, leads to spurious results if not addressed.Supplemental Digital Content is available in the text.